2019
DOI: 10.1186/s12884-018-2167-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fetal growth velocities and the association with neonatal outcomes in appropriate-for-gestational-age neonates: a retrospective cohort study

Abstract: BackgroundFetal growth restriction is, despite advances in neonatal care and uptake of antenatal ultrasound scanning, still a major cause of perinatal morbidity. Neonates with birth weight > 10th percentile are assumed to be appropriate-for-gestational-age (AGA), although many are at increased risk of perinatal morbidity, because of undetected mild restriction of growth potential. We hypothesized that within AGA neonates, reduced fetal growth velocities are associated with adverse neonatal outcome.MethodsA ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…We and others have demonstrated the added value of combining the measurement of placental biomarkers in the first trimester with clinical characteristics, Doppler parameters or fetal growth in the prediction of FGR. 38,43,44 The use of multiple parameters could increase the specificity and sensitivity of the screening, mainly because each biomarker reflect a different mechanistic pathway linked to the disease process. While abnormal uterine artery Doppler reflects the inadequate trophoblastic invasion of the maternal spiral arteries, abnormal serum concentrations of PlGF and sFlt-1 reflect the dysregulated secretory activity by placental trophoblasts, 6 both well recognized mechanisms linked to the development of FGR.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated the added value of combining the measurement of placental biomarkers in the first trimester with clinical characteristics, Doppler parameters or fetal growth in the prediction of FGR. 38,43,44 The use of multiple parameters could increase the specificity and sensitivity of the screening, mainly because each biomarker reflect a different mechanistic pathway linked to the disease process. While abnormal uterine artery Doppler reflects the inadequate trophoblastic invasion of the maternal spiral arteries, abnormal serum concentrations of PlGF and sFlt-1 reflect the dysregulated secretory activity by placental trophoblasts, 6 both well recognized mechanisms linked to the development of FGR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sensitivity analysis showed that EFW velocity in the bottom 10th percentile was significantly associated with more adverse perinatal outcomes (including preterm birth < 37 weeks, admitted to NICU, neonatal complications) in the AGA group than the LGA and SGA groups. Hendrix et al [ 32 ] reported similar findings, i.e., decreased fetal growth velocities between around 20 and 32 weeks were significantly associated with adverse neonatal outcomes (neonatal asphyxia, sepsis, respiratory distress syndrome, and transient shortness of breath) in AGA neonates. In a prospective cohort of 3977 pregnant women, Sovio et al [ 33 ] found that, compared to EFW velocity alone in the bottom 10th percentile, AC velocity in the lowest decile was also associated with a higher relative risk of SGA and other adverse perinatal outcomes.…”
Section: Discussionmentioning
confidence: 77%
“…Hendrix et al evaluated infants in whom weight was appropriate for gestational age (AGA), defined as birthweight >10%ile and found that abnormal fetal growth velocities, especially abdominal circumference velocity, was associated with adverse neonatal outcomes. 22 This study concluded that using EFW < 10%ile alone in ultrasound evaluation may miss mild restriction of growth potential. Although limited studies have specifically compared neonatal outcomes in pregnancies complicated by fetal growth restriction versus those with transient fetal growth restriction, there have been studies…”
Section: Discussionmentioning
confidence: 83%